2014
DOI: 10.1016/j.clinph.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity during complex imagined gait tasks in Parkinson disease

Abstract: Objective Motor imagery during functional magnetic resonance imaging (fMRI) allows assessment of brain activity during tasks, like walking, that cannot be completed in a scanner. We used gait imagery to assess the neural pathophysiology of locomotion in Parkinson disease (PD). Methods Brain activity was measured in five locomotor regions (supplementary motor area (SMA), globus pallidus (GP), putamen, mesencephalic locomotor region, cerebellar locomotor region) during simple (forward) and complex (backward, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 74 publications
(130 reference statements)
4
51
0
4
Order By: Relevance
“…Similar activation patterns between Parkinson patients and healthy controls have been found in subcortical areas (Peterson et al, 2014b), but also in cortical areas On the other hand, the observed hyperactivations seem to depend on the complexity of gait imagination tasks as higher activity was found in SMA during imagining turning to the left/right (Peterson et al, 2014b), right dorsal premotor areas, precentral right inferior parietal lobule and bilaterally precuneus and MT/V5 during imagery of gait initiation, walking over obstacles and gait termination (Wai et al, 2012). Also, Cremers et al (2012) showed that the activity in the right posterior parietal cortex including right intraparietal sulcus, superior parietal lobule, adjacent precuneus and pre-SMA decreases greater, when the severity of the gait disorders increases (see Table 5).…”
Section: 2 Brain Activity Of Neurological Patients (Parkinson Diseasupporting
confidence: 52%
See 4 more Smart Citations
“…Similar activation patterns between Parkinson patients and healthy controls have been found in subcortical areas (Peterson et al, 2014b), but also in cortical areas On the other hand, the observed hyperactivations seem to depend on the complexity of gait imagination tasks as higher activity was found in SMA during imagining turning to the left/right (Peterson et al, 2014b), right dorsal premotor areas, precentral right inferior parietal lobule and bilaterally precuneus and MT/V5 during imagery of gait initiation, walking over obstacles and gait termination (Wai et al, 2012). Also, Cremers et al (2012) showed that the activity in the right posterior parietal cortex including right intraparietal sulcus, superior parietal lobule, adjacent precuneus and pre-SMA decreases greater, when the severity of the gait disorders increases (see Table 5).…”
Section: 2 Brain Activity Of Neurological Patients (Parkinson Diseasupporting
confidence: 52%
“…Also, Cremers et al (2012) showed that the activity in the right posterior parietal cortex including right intraparietal sulcus, superior parietal lobule, adjacent precuneus and pre-SMA decreases greater, when the severity of the gait disorders increases (see Table 5). Furthermore, a positive correlation between faster gait velocity and activities in the SMA, putamen, MLR and pallidum was observed for the Parkinson patients (Peterson et al, 2014b). Snijders et al (2011) showed a connection between greater step lengths and activity in the SMA, which, however, was only so for controls (see Table 5).…”
Section: 2 Brain Activity Of Neurological Patients (Parkinson Diseamentioning
confidence: 76%
See 3 more Smart Citations